Ultrahigh‐Output Triboelectric and Electromagnetic Hybrid Generator for Self‐Powered Smart Electronics and Biomedical Applications (Adv. Energy Mater. 40/2022). Issue 40 (27th October 2022) - Rana, S. M. Sohel; Salauddin, M.; Sharifuzzaman, Md; Lee, Sang Hyun; Shin, Young Do; Song, Hyesu; Jeong, Seong Hoon; Bhatta, Trilochan; Shrestha, Kumar; Park, Jae Yeong
Abstract : Hybrid Nanogenerators In article number 2202238, Jae Yeong Park and co‐workers successfully developed ultra‐high output hybridized nanogenerators based on triboelectric and electromagnetic generators to scavenge biomechanical energy and provide a self‐powered system. Halbach magnet arrays improve electromagnetic generator performance by concentrating magnetic flux in the coil, while polyethylene oxide nanofibers improve triboelectric performance. The fabricated device demonstrates biomechanical energy harvesting and provides a fast‐charging power source for portable electronics.